Kepemimpinan dalam Pendidikan Kristen untuk Pendewasaan Warga Gereja Kemah Injil (Kingmi) di Tanah Papua - Asso, Ardi; Pigai, Fredi; Watipo, Arson (Harati: Jurnal Pendidikan Kristen, 2023)
This research aims to analyze the function of leadership in Christian education for the maturation of Kemah Injil Church (KINGMI) congregations in Tanah Papua. This research uses a quantitative method with a descriptive correlational approach. Data were collected through interviews and questionnaires. The results revealed that the tendency of pastors to be active educational leaders has a "moderate impact on the maturation of members of the Kemah Injil Church (KINGMI) in Papua," which is significant at α>0.05. Based on the results of data processing, the influence of educational background relationship in the "strong" category on the maturity of Kemah Injil Church (KINGMI) members in the Land of Papua, which is significant at α>0.05.